KUAT TEKAN SELF COMPACTING CONCRETE MENGGUNAKAN GROUND GRANULATED BLAST FURNACE SLAG - Anni Susilowati; pratikto pratikto; Dennis Yudha Praditya; Kusno Wijayanto (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2019)
Self Compacting Concrete (SCC) as one type of concrete that is mostly used in building construction has good workability and can be obtained by adding filler instead of cement. Ground Granulated Blast Furnace Slag (GGBFS) has a chemical composition similar to the content in cement. Therefore, the study of the use of GGBFS was used as a partial substitute for cement in the SCC to examine the influences and quality of GGBFS on fresh concrete and to obtain SCC with the best compressive strength. This research method uses an experimental method by making SCC concrete specimens with an initial fas of 0.4 according to ACI 211.4R-93. The specimens were worked using GGBFS levels of 0%, until 80%, and using 1,4% superplasticizer, and 2% accelerator by weight of cement. The use of GGBFS at SCC can increase the value of compressive strength of about 4,27%-25,64 compared to SCC without using GGBFS. The resulted are known that GGBFS can influence compression strength. Based on the testing of fresh and hard concrete, it concluded that the best quality of SCC used 20% of GGBFS.